Мethodological function of philosophy in the paradigm of education of the xxi century - Volovchuk, N. (Problems of Engineer-Pedagogical Education, 2019)
The article discusses the modern challenges to science and education against a background of global cataclysms of the twentieth century (world crises, wars, man-made disasters, economic contradictions of developed and developing countries, social stratification), as well as the crisis of the worldview and humanitarian component of culture, expressed in the crisis of the ideas of the University. Challenges coming from both internal (the need to develop and transmit knowledge) and external factors (state and non-state actors) actualize the potential of philosophy as holistic, critical, discursive knowledge to cope with current threats and anticipate new ones. On the basis of the dialectical approach, the research has proved that overcoming the utilitarian-pragmatic nature of the modern education paradigm is possible through the inclusion of philosophical disciplines in the curriculum, since philosophy is metacognition affecting the premise of scientific knowledge, and a vital structural element providing a methodological, conceptual, and ideological base in education focused on the value approach, on realization of the unity of the ethical component and scientific knowledge, on obtaining fundamental knowledge and beliefs.